2019
DOI: 10.1063/1.5088770
|View full text |Cite
|
Sign up to set email alerts
|

An extension of the fewest switches surface hopping algorithm to complex Hamiltonians and photophysics in magnetic fields: Berry curvature and “magnetic” forces

Abstract: We present a preliminary extension of the fewest switches surface hopping (FSSH) algorithm to the case of complex Hamiltonians as appropriate for modeling the dynamics of photoexcited molecules in magnetic fields. We make ansätze for the direction of momentum rescaling and we account for Berry's phase effects through "magnetic" forces as applicable in the adiabatic limit. Because Berry's phase is a nonlocal, topological characteristic of a set of entangled potential energy surfaces, we find that Tully's local … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 71 publications
(102 reference statements)
0
43
0
Order By: Relevance
“…FSSH dictates motion along adiabats and the algorithm will not predict any bending or reflection; for this reason, in Ref. 37, we have recommended augmenting FSSH dynamics with the Berry force F B (in Eq. 6) in order to better agree with the QCLE and capture the correct quantum dynamics.…”
Section: Discussion: Implications For Semiclassical Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…FSSH dictates motion along adiabats and the algorithm will not predict any bending or reflection; for this reason, in Ref. 37, we have recommended augmenting FSSH dynamics with the Berry force F B (in Eq. 6) in order to better agree with the QCLE and capture the correct quantum dynamics.…”
Section: Discussion: Implications For Semiclassical Dynamicsmentioning
confidence: 99%
“…Unfortunately, preliminary evidence suggests that the algorithms in Ref. 37 are not yet optimal; perhaps the different form of the QCLE (as present in Eqs. 5 and A1) will be useful for future derivations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent dynamical work has suggested that the imaginary component of NADCs can yield very rich new physical behaviors. 42 In particular, whenever the derivative coupling d is complex, such complexity automatically introduces nontrivial Berry phase effects, 72,73 whereby a given trajectory moving on adiabat J with momentum ⃗ p should feel a force, 42,74…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, one must presume that semiclassical mechanics are possible with complex NADCs, and a recent work has explored various ansätze for the extension of FSSH with complex-valued NADCs. 42 Since the overall phases of the adiabats are not well defined, the total phase of the derivative coupling is not well-defined, and choosing a direction of momentum rescaling is not obvious. Previous work in Ref.…”
Section: Article Scitationorg/journal/jcpmentioning
confidence: 99%
See 1 more Smart Citation